Pengaruh Pengungkapan CSR Terhadap Nilai Perusahaan dengan Profitabilitas, Leverage, dan Likuiditas Sebagai Moderasi pada Sektor Perbankan di BEI Tahun 2020-2024 - Shankisma Bela Negara; Djeni Indrajati Widjaja (Ikatan Da'i Indonesia, 2026)
This inquiry aims to empirically examine the leverage of Corporate Social Responsibility (CSR) disclosure on corporate worth, while positioning profitability, leverage, and liquidity as potential moderating metrics. Focusing on the banking firms registered on the Indonesia Stock Exchange (IDX) spanning 2020–2024, this empirical study gathered 15 banks as research samples. The structural parameters were calculated using Moderated Regression Analysis (MRA). The empirical insights indicate that CSR disclosure exerts no meaningful effect on firm value. Furthermore, internal financial attributes—namely profitability, leverage, and liquidity—fail to significantly moderate the interaction between CSR reporting and the market valuation of banking firms.